Frugivory and habitat use by fruit-eating birds in a fragmented landscape of southeast Brazil - Pizo, M. A. (2004)
To investigate the movement of seeds transported by fruit-eating birds in an agricultural, fragmented landscape of the Atlantic forest of southeast Brazil, I asked which bird species are the main seed dispersers in such environment, and how they use the available habitats (small forest fragments, forest thickets, live fences, isolated trees, and active pastures) where they are most likely to drop the seeds they swallow the relative importance of fruit-eating birds as seed vectors was evaluated based on the number of fruit species eaten, the number of visits, and visitation rate to fruiting plants. Habitat use was accessed by recording the habitats where birds were seen or heard during walks conducted throughout the study area. Sixteen plant species were observed during 308.3 plant-hours. Forty-one bird species were observed eating fruits in a total of 830 visits to fruiting plants. Sayaca Tanagers (Thraupis sayaca) and Pale-breasted Thrushes (Turdus leucomelas) ate the greatest number of fruit species, were the most frequent plant visitors in terms of number and rate of visits, and had a broad range of habitat use. These two species and the Rusty-margined Guan (Penelope superciliaris), which is able to swallow large fruits with large seeds that smaller bird species cannot cat, likely have a great contribution to the movement of seeds throughout this highly degraded landscape.